The impact of POS materials on sales : LEGO Nexo Knights 2016 campaign in toy specialist stores - Kinštová, Veronika; Král, Petr, 1979-; Karlíček, Miroslav, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
In today's highly competitive and cluttered marketing environment it becomes increasingly harder for brands to differentiate themselves form others. This is especially pronounced in the retail space. Shopper marketing is a discipline that focuses on shoppers and their needs to create a unique shopping experience and thereby increase in-store communication effectiveness. Keeping in mind the challenges of marketing to children, LEGO aims to communicate to its shoppers as well as consumers through the platform of in-store its core values of creative play, fun and learning. The thesis discusses the effectiveness of LEGO shopper marketing, specifically the engagement elements it uses in various channels. The aim is to test and evaluate the impact of these materials on the target audience and sales as well as define the hierarchy of LEGO in-store communication materials. In the theoretical part shopper marketing concepts, shopper beaviour and marketing in the toy industry are discussed.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses